Extrinsic motivation index: A new tool for managing labor productivity - Sergio A. Berumen; Luis P. Pérez-Megino; Karen Arriaza Ibarra (International Journal of Business Science & Applied Management (IJBSAM), 2016)
The objective of this paper is to provide a tool of practical significance for HR managers and firm executives. This tool, which is called Extrinsic Motivation Index (EMI), is meant to measure the extrinsic motivation of employees. By measuring employees' extrinsic motivation, managers are able to track job satisfaction and, subsequently, implement measures aiming both to raise job satisfaction and to improve organizational commitment. In order to test the validity of the model, we apply the EMI to Faculty members at Spanish and German universities. We also carry out simulation experiments in order to to address all possible situations an organization most probably will have to deal with. The results point out significant differences in the level of motivation and commitment of Faculty members. Additionally, the analysis shows several ways in which an organization may manage job satisfaction issues according to on its level of resources.
Keywords: 650; motivation; job satisfaction; human resources; statistical methods